What is the Supreme Court? - Abramson, Jill, 1954-; Copeland, Gregory (New York : Penguin Workshop, 2022)
Ever since it was established, the United States Supreme Court has had a major impact on the lives of all Americans. Some of its landmark decisions have helped end segregation, protected a person's privacy, and allowed people to marry whomever they love. This book explains how the highest court in the United States works, who gets to serve on it, which cases have had the greatest impact on the country, and why the US justice system is so vital to democracy.
What Is the Supreme Court? -- What Is the judiciary? -- The first Monday in October -- Beginnings -- The worst decision ever -- Separate but equal? -- Packing the court -- A decision for Linda Brown -- Rights of the accused -- Marriage and protest -- The 2000 Presidential Race -- No longer a "men's club" -- It is so ordered.
Includes bibliographical references (page 108).
3-6
940L
6.0
Keywords: United States. -- Supreme Court -- Juvenile literature; Constitutional history -- United States -- Juvenile literature; United States, Supreme Court; United States, Supreme Court -- History; Justice, Administration of -- United States